Smile makeover for multiple caries of anterior teeth through endodontic, periodontic, and restorative management: a case report - Anindya, Cinitra; Widjaja, Olivia Vivian; Ismiyatin, kun; Saraswati, Widya; Setyabudi (Universitas Airlangga, 2024)
Background: Dental aesthetic issues may affect individual’s aesthetic, function, and psychological well-being. The functions of the stomatognathic system are supporting mastication, speaking, breathing and swallowing functions, so that structural integrity and an ideal and harmonious smile can be achieved as well. Aesthetic issues due to caries of maxillary anterior teeth requires deep analysis, consideration and appropriate treatment planning to aim a good result both functionally and aesthetically. Digital smile design (DSD) plays an important role in aesthetic dentistry where problems can easily be rectified. Purpose: This case report describes a step-by-step aesthetic treatment of a male patient with multiple caries of anterior teeth. Case: This study reports a 21-year-old man with multiple caries on his maxillary anterior teeth. Tooth number 12 with class IV caries lesion. Teeth number 11 and 22 with class IV and VI caries lesion and were endodontically treated, tooth number 21 with class III mesiodistal caries lesion. The patient’s chief complaint is that he felt less confidence with his appearance. Case Management: tooth number 21 was managed with endodontic treatment and followed by insertion of fiber post. Teeth number 11 and 22 that endodontically treated previously, were managed with prefabricated fiber post. Tooth number 12 was managed with crown. Teeth number 11, 21, 22 11, 21, 22 were managed with gingivectomy for aesthetic crown lengthening. Lithium disilicate was chosen for the crown materials Conclusion: Anterior teeth with multiple caries can be improved through endodontic-periodontal-restoration treatments to improve the function and aesthetic performance.